2012
DOI: 10.1258/ht.2012.012003
|View full text |Cite
|
Sign up to set email alerts
|

Use of audiovisual equipment (SKYPE) for the treatment of hand injuries for remote consultations

Abstract: Introduction. We present this case of a British patient living and working in Africa who used audiovisual (SKYPE) equipment as a treatment option for remote consultation. This was investigated in response to a request by the patient for further postoperative support at a distance after a complex hand surgery procedure. Methods. Audiovisual (SKYPE) equipment was used by the team in combination with manual therapy as a means of seeking advice, progressing treatment and liaison with a specialist hand therapist an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…17 Table 5 demonstrates the quality assessment for the qualitative study, 28 which had low risk of bias. Table 6 presents an evaluation of risk of bias for two case series, 22,29 which had overall high risk of bias. Table 7 demonstrates risk of bias findings for intervention studies, evaluated with the Cochrane risk of bias tool.…”
Section: Resultsmentioning
confidence: 99%
“…17 Table 5 demonstrates the quality assessment for the qualitative study, 28 which had low risk of bias. Table 6 presents an evaluation of risk of bias for two case series, 22,29 which had overall high risk of bias. Table 7 demonstrates risk of bias findings for intervention studies, evaluated with the Cochrane risk of bias tool.…”
Section: Resultsmentioning
confidence: 99%
“…The study concluded that Skype enabled the allied health team to communicate with specialists and patients reported positive clinical outcomes, including a reduction in anxiety regarding the management of serious hand injuries. 2 Another case report relating to an inpatient palliative service described the use of Skype to communicate with family and friends. The study found that communication using Skype was feasible, and both patients and families had high satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, a need to invest in access to audio-visual technology and equipment: Although previous studies have highlighted that subsets of patients could benefit from the use of audio-visual consultations, 13,14 limited uptake prior to the pandemic was noted, with only 16% of services reporting pre-existing digital services. Whilst rapid service developments were expected to bring challenges, significant delays in the ability to offer audio-visual consultation were reported, with an average of 28 days taken to be operational.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it could be effective for vulnerable groups such as prisoners, deployed UK personnel, those facing long journeys for review, and for continuity in care during inclement weather and disease outbreak. 13 Investigation into inclusive strategies to ensure equitable access for patients to the use of technology-enabled care should be prioritised by NHS leadership. Particular attention should be given to legal implications and consent.…”
Section: Discussionmentioning
confidence: 99%